2004
DOI: 10.1161/01.cir.0000105720.28086.6c
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Reduced Antioxidative Protection and Increased Ischemic Heart Disease Risk

Abstract: Background-Extracellular superoxide dismutase (EC-SOD) is an antioxidative enzyme found in high concentrations in the arterial wall. Two to three percent of all people in Denmark carry an R213G substitution, which increases plasma concentration 10-fold. This may reduce arterial wall EC-SOD concentrations, increase intimal LDL oxidation, and therefore may accelerate atherogenesis. Our primary hypothesis was that EC-SOD-R213G predisposes to ischemic heart disease (IHD). The secondary hypothesis was that EC-SOD-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
123
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 19 publications
11
123
0
5
Order By: Relevance
“…120 Also, the R213G gene variant was suggested to accelerate the progression of renal failure and atherosclerosis in uremic patients. 121 Finally, a study in Denmark detected a 2.3-fold increase in risk of ischemic heart disease in heterozygotes carrying ecSOD(R213G), with a 9-fold increase for plasma levels of ecSOD, 122 presumably because of increased in the vasculature of ecSOD(R213G) carriers.…”
Section: Ecsod Gene Variantsmentioning
confidence: 99%
“…120 Also, the R213G gene variant was suggested to accelerate the progression of renal failure and atherosclerosis in uremic patients. 121 Finally, a study in Denmark detected a 2.3-fold increase in risk of ischemic heart disease in heterozygotes carrying ecSOD(R213G), with a 9-fold increase for plasma levels of ecSOD, 122 presumably because of increased in the vasculature of ecSOD(R213G) carriers.…”
Section: Ecsod Gene Variantsmentioning
confidence: 99%
“…3 Consequently, a role of endogenous ecSOD for controlling NO bioavailability has been demonstrated in animal experiments 4 and a mutation of ecSOD which attenuates binding of the enzyme to matrix, is associated with an increased risk of cardiovascular fatalities. 5 It is unclear whether pharmacological application of human ecSOD confers protection against oxidative stress in the vasculature. Most studies reporting a beneficial effect were performed in rats.…”
Section: See Page 442mentioning
confidence: 99%
“…As a result, EC-SOD binds to the surface of endothelial cells and the extracellular matrix which has a high abundance of heparan sulfate [6]. Patients in whom EC-SOD binding to endothelial cells is decreased as the result of substitution of arginine-213 by glycine (R213G) have an increased incidence of hypertension [7] and increased risk of ischemic heart disease [7,8], implying that impaired EC-SOD binding or decreased myocardial EC-SOD content can increase the vulnerability to cardiovascular disease. Several recent studies have demonstrated that EC-SOD expression is decreased in the failing heart, and this was associated with evidence of increased myocardial oxidative stress and endothelial dysfunction [9][10][11].…”
Section: Introductionmentioning
confidence: 99%